High-performance single-atom M/TiO2 catalysts in the reverse water-gas shift reaction: A comprehensive experimental and theoretical investigation - Moshood O. Bolarinwa; Aasif A. Dabbawala; Shamraiz Hussain Talib; Georgian Melinte; Thomas Delclos; Abdulmuizz Adamson; Abbas Khaleel; Kyriaki Polychronopoulou; Dalaver H. Anjum (Journal of CO2 Utilization)
Single-atom catalysts (SACs) offer high efficiency and selectivity in chemical reactions but face challenges in converting CO2 to CO via the reverse water gas shift (RWGS) reactions. This study addresses these challenges by anchoring three noble metals (Ir, Pd, and Ru) onto titania (TiO2) and analyzing their performance. Comprehensive characterization techniques, including electron microscopy, confirmed the uniform dispersion of metal atoms on TiO2. Among the catalysts, Ir/TiO2 exhibited the best results, achieving an 84 % CO2 conversion rate and ∼98 % CO selectivity, surpassing Pd/TiO2 and Ru/TiO2, which gained 56 % and 52 % conversion, respectively. In-situ gas transmission electron microscopy revealed the catalytic behavior of Ir/TiO2, showing Ir atom mobility and the formation of ∼1 nm nanoclusters. Density functional theory (DFT) and in-situ diffuse reflectance infrared spectroscopy (DRIFTs) further explained that the atomically dispersed Ir sites in Ir/TiO2 follow a hydrogen-assisted mechanism, with the COOH* intermediate desorbing and dissociating into CO. These findings suggest SACs' potential to facilitate greener chemical processes and reduce greenhouse gas emissions.